2021
DOI: 10.3758/s13414-021-02333-x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and pitfalls of data compression in visual working memory

Abstract: Data compression in memory is a cognitive process allowing participants to cope with complexity to reduce information load. However, previous studies have not yet considered the hypothesis that this process could also lead to over-simplifying information due to haphazard amplification of the compression process itself. For instance, we could expect that the over-regularized features of a visual scene could produce false recognition of patterns, not because of storage capacity limits but because of an errant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Previous studies in the visual domain have shown that compression, although enhancing WM precision, can also lead to drawbacks (Haladjian & Mathy, 2015; Nassar et al, 2018). For instance, it has been shown that compression may lead to an oversimplification of information, thereby increasing the proportion of false recognition for more compressible sequences (Lazartigues et al, 2021). Similarly, participant’s responses in visual array tasks appear to be biased toward the mean of the ensemble representation (Brady & Alvarez, 2011; Son et al, 2020), suggesting that some of the original representation is potentially lost during the compression process.…”
Section: Between-item Similarity Supports the Temporary Maintenance O...mentioning
confidence: 99%
“…Previous studies in the visual domain have shown that compression, although enhancing WM precision, can also lead to drawbacks (Haladjian & Mathy, 2015; Nassar et al, 2018). For instance, it has been shown that compression may lead to an oversimplification of information, thereby increasing the proportion of false recognition for more compressible sequences (Lazartigues et al, 2021). Similarly, participant’s responses in visual array tasks appear to be biased toward the mean of the ensemble representation (Brady & Alvarez, 2011; Son et al, 2020), suggesting that some of the original representation is potentially lost during the compression process.…”
Section: Between-item Similarity Supports the Temporary Maintenance O...mentioning
confidence: 99%
“…However, it could also be the case that some form of compression mechanism already operates at the level of WM representations (i.e., when constructing the event model of the current situation). Between event boundaries, the continuous unfolding of experience could be summarized through WM processes, enabling the construction of event models covering longer time spans, but in a format further away from reality/perception (Al Roumi et al, 2021;Brady et al, 2009;Lazartigues et al, 2021). Indeed, previous studies have shown that visuospatial information (e.g., spatial sequences, multidimensional objects, or color-changing shapes) that includes regularities tends to be compressed in WM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the visual domain, some studies suggest that individuals utilize such structural dependencies to simplify their mental representation of stimuli to allow their retention in memory. This is thought to take different forms, with individuals encoding both detailed information about specific items and the overall summary of a scene (Brady & Tenenbaum, 2013; Hollingworth & Henderson, 2003; Oliva, 2005), or by regularizing the features of a scene to facilitate compressibility and reduce short-term memory (STM) load—though such compression may also cause memory errors by oversimplifying the data (Lazartigues et al, 2021). Yet other studies have challenged the notion of chunking as a form of data compression that frees up working memory (Norris et al, 2020), and instead suggest that chunking may be achieved by redintegration.…”
Section: Discussionmentioning
confidence: 99%